Model Kooperatif Teams Games Tournaments: Apakah dapat meningkatkan keterampilan belajar dribbling sepakbola? - Wildani, Lutfi; Gazali, Novri (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2020)
This study aims to improve learning skills for soccer dribbling in class XI IPA 3 SMA Negeri 12 Pekanbaru by using the TGT (Teams Games Tournaments) type cooperative model. This type of research uses Classroom Action Research. The subjects of this study were 20 people consisting of 15 male students and 5 female students. The results showed that in cycle I there were 7 students who completed with a percentage of 35% and students who did not complete were 13 students with a percentage of 65%, while in cycle II there were 16 students who completed with a percentage of 80% and students who did not complete as many as 4 people with a percentage of 20%. Based on the results of research conducted through a 2-cycle process, it is concluded that the cooperative model type TGT (Teams Games Tournaments) can improve the football dribbling skills of class XI IPA 3 students of SMA Negeri 12 Pekanbaru. It is hoped that the TGT (Teams Games Tournaments) type of cooperative model can also be applied to all sports that are studied in schools.